Gram-negative bacteraemia; a multi-centre prospective evaluation of empiric antibiotic therapy and outcome in English acute hospitals. (March 2016) - Fitzpatrick, J.M.; Biswas, J.S.; Edgeworth, J.D.; Islam, J.; Jenkins, N.; Judge, R.; Lavery, A.J.; Melzer, M.; Morris-Jones, S.; Nsutebu, E.F.; Peters, J.; Pillay, D.G.; et al.
Abstract: Increasing antibiotic resistance makes choosing antibiotics for suspected Gram-negative infection challenging. This study set out to identify key determinants of mortality among patients with Gram-negative bacteraemia, focusing particularly on the importance of appropriate empiric antibiotic treatment. We conducted a prospective observational study of 679 unselected adults with Gram-negative bacteraemia at ten acute english hospitals between October 2013 and March 2014. Appropriate empiric antibiotic treatment was defined as intravenous treatment on the day of blood culture collection with an antibiotic to which the cultured organism was sensitive in vitro . Mortality analyses were adjusted for patient demographics, co-morbidities and illness severity. The majority of bacteraemias were community-onset (70%); most were caused by Escherichia coli (65%), Klebsiella spp. (15%) or Pseudomonas spp. (7%). Main foci of infection were urinary tract (51%), abdomen/biliary tract (20%) and lower respiratory tract (14%). The main antibiotics used were co-amoxiclav (32%) and piperacillin–tazobactam (30%) with 34% receiving combination therapy (predominantly aminoglycosides). Empiric treatment was inappropriate in 34%. All-cause mortality was 8% at 7 days and 15% at 30 days. Independent predictors of mortality (p <0.05) included older age, greater burden of co-morbid disease, severity of illness at presentation and inflammatory response. Inappropriate empiric antibiotic therapy was not associated with mortality at either time-point (adjusted OR 0.82; 95% CI 0.35–1.94 and adjusted OR 0.92; 95% CI 0.50–1.66, respectively). Although our study does not exclude an impact of empiric antibiotic choice on survival in Gram-negative bacteraemia, outcome is determined primarily by patient and disease factors.